2013
DOI: 10.26530/oapen_578133
|View full text |Cite
|
Sign up to set email alerts
|

Leak Detection: Technology and Implementation

Abstract: Texas-based New Braunfels Utilities (NBU) used a range of leak detection equipment manufactured by HWM to build an efficient maintenance program for its distribution network while drastically reducing water loss. The equipment has allowed NBU to conduct scheduled repairs on its pipelines instead of dealing with leaks on an emergency basis. The team began using this equipment to perform preventive maintenance on 750 valves per year and proactively scan the city for non-surfacing leaks. 5.1.5 Results obtained Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 2 publications
2
29
0
1
Order By: Relevance
“…Fan et al () found that customer consumption changes more slowly with respect to duty cycle when t ∈[0.25,1]. Similarly, Hamilton and Charalambous () report that the total customer consumption reduced by only 15% when the duty cycle was reduced from t =1→0.25 in Limassol, Cyprus. Therefore, in this simple model, daily customer demand (which is not always met) will be considered independent of duty cycle.…”
Section: Model Constructionmentioning
confidence: 98%
“…Fan et al () found that customer consumption changes more slowly with respect to duty cycle when t ∈[0.25,1]. Similarly, Hamilton and Charalambous () report that the total customer consumption reduced by only 15% when the duty cycle was reduced from t =1→0.25 in Limassol, Cyprus. Therefore, in this simple model, daily customer demand (which is not always met) will be considered independent of duty cycle.…”
Section: Model Constructionmentioning
confidence: 98%
“…In general, there are two categories of leakage detection methods, namely device-based and model-based methods. Among various device-based methods (Hamilton and Charalambous 2013) for finding leaks, step-testing and acoustic noise logging methods are probably the most widely-used. For efficient deployment of resources, it is preferable to have the identification of potential leakage hotspot areas before sending the leakage detection crew into the field to find leaks.…”
Section: Introductionmentioning
confidence: 99%
“…These data are used for operational control of the pipeline. They can be used also for detection of unpredictable pipeline depressurization, leakage location and its identification [1,2]. In this connection, we can mention two known methods of leak detection in gas pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is so called method of negative pressure waves [1][2][3]. The idea of the method is that the sharp pressure jump, emergent at the depressurization point, produces two waves of negative pressure This work was supported by grants of NASU, State registration 0113U007687 and 0116U007435.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation